AN INVESTIGATION INTO INSTRUCTIONS IN CAMBRIDGE TESTS - NGUYỄN THỊ HIỀN LINH (2015)
This is a corpus-based study on syntactic, semantic and pragmatic features of instructions in Cambridge Tests. An investigation is made to find out how the structures have been used in English as well as provide a better understanding of the function of syntactic forms used in instructional text. The data of the study are collected from the practice tests in Cambridge systems such as: KET, PET, FCE, CAE and CPE. The data are described and analyzed basing on qualitative and quantitative methods. Together with the analysis, a discussion and comments on syntactic and semantic features have been made. The thesis also suggests some guidelines for further researches on different fields of instructions in testing so that other authors study deeper the interesting areas of instructions in language testing.
Keywords: NGUYỄN THỊ HIỀN LINH, AN INVESTIGATION INTO INSTRUCTIONS IN CAMBRIDGE TESTS, INSTRUCTIONS IN CAMBRIDGE TESTS, CAMBRIDGE TESTS